Reconstruction of Law Enforcement in Indonesia Through Strengthening the Embodiment of Pancasila Values of Justice to Realize Humane Law Enforcement - Fajar Bima Alfian (Fakultas Hukum Universitas Lampung, 2022)
The development of globalization has had both positive and negative impacts on all sectors in its implementation, especially law enforcement in Indonesia. The practice of law enforcement so far has continued without an adequate foundation, giving rise to injustice. Therefore, efforts are needed as preventive and curative steps, namely strengthening the realization of Pancasila justice in law enforcement to realize humane law enforcement, especially within the prosecutor's office. The research method used in this paper is normative juridical with a philosophical approach, a conceptual approach,, and a case approach. The results obtained are that law enforcement must prioritize the application of the noble values of Pancasila, which is balanced with the application of a philosophy of punishment based on the concept of restorative justice, which justice to frame various existing policies, so that the results of these policies can create a sense of justice that perpetrators feel, victims, the public and answer various problems in the judiciary and lead to the creation of humane prosecutors, besides that the values of Pancasila must be attached to law enforcers, especially prosecutor's profession. Judges decide cases with the direction